2016
DOI: 10.1016/j.jep.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedical research and review of Q’eqchi Maya women's reproductive health in the Lake Izabal region of Guatemala: Past, present and future prospects

Abstract: Ethnopharmacological relevance In Central America, most Maya women use ethnomedicines for all aspects of their reproductive cycle including menstruation, pregnancy and menopause. However, very few of these plants have been documented, collected and tested in appropriate pharmacological assays to determine possible safety and efficacy. The aim of this work was to provide an overview of information on the ethnomedical uses, ethnopharmacology, chemistry and pharmacological research for medicinal plants used for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 130 publications
0
7
0
Order By: Relevance
“…The use of medicinal plants by the Q'eqchi' of Guatemala has been the subject of previous studies using different approaches, some of the most recent being studies on a specific species to treat the culture-bound illness “susto” (Mullally et al, 2016 ), the antifungal activity of a single species (Ta et al, 2016 ), the diagnosis of the single culture-bound illness “emplotment” (Hatala and Waldram, 2017 ), the investigation and review of Q'eqchi women's reproductive health in the Lake Izabal region (Michel et al, 2016 ), the broad study of Mayan phytomedicine in Guatemala and a further proposal for patient-centered boundary mechanisms to foster intercultural partnerships in health care (Hitziger et al, 2016 , 2017 ). The present study differs from these previous studies because it was conducted in three communities of Alta Verapaz with a normal population (no traditional healers).…”
Section: Introductionmentioning
confidence: 99%
“…The use of medicinal plants by the Q'eqchi' of Guatemala has been the subject of previous studies using different approaches, some of the most recent being studies on a specific species to treat the culture-bound illness “susto” (Mullally et al, 2016 ), the antifungal activity of a single species (Ta et al, 2016 ), the diagnosis of the single culture-bound illness “emplotment” (Hatala and Waldram, 2017 ), the investigation and review of Q'eqchi women's reproductive health in the Lake Izabal region (Michel et al, 2016 ), the broad study of Mayan phytomedicine in Guatemala and a further proposal for patient-centered boundary mechanisms to foster intercultural partnerships in health care (Hitziger et al, 2016 , 2017 ). The present study differs from these previous studies because it was conducted in three communities of Alta Verapaz with a normal population (no traditional healers).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the broad categories “digestive” (D) and “skin” (S) are among those with the highest number of associated medicinal plants and use-records ( Table 2 ). Musculoskeletal ailments (L) are often treated with massages by traditional healers called ‘ sobadores ’ or ‘ ajpamaj ’ ( Ankli et al., 1999 ; Leonti et al., 2001 ; Berger-González et al., 2016b ; Geck et al., 2016 ) while midwifes give massages for problems of the lower female organs (X) ( Weimann and Heinrich, 1997 ; Ankli et al., 1999 ; Michel et al., 2016 ). Measures for family planning (W) are provided by the IMSS in collaboration with MEXFAM.…”
Section: Resultsmentioning
confidence: 99%
“…Formal sex education was not available for adolescent Maya girls, and conversations about sexuality were taboo among family members (Michel, Caceres, & Mahady, 2016; Wehr & Tum, 2013). Birth control methods were not used due to cultural norms, embarrassment, or belief that girls were not at risk for sexually transmitted infections (Wehr & Tum, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other investigators reported that discussing reproductive symptoms, such as menstruation, pregnancy, and menopause, was taboo in the Maya culture. Women relieved these symptoms with herbal remedies, yet safe use and efficacy of these herbs remained a concern (Michel et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%